Austerity, Inequality, and Private Debt Overhang - Mathias Klein; Roland Winkler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We show that the distributional consequences of fiscal consolidations depend significantly on the level of private indebtedness. Austerity leads to a strong and persistent increase in income inequality when private debt is high. In contrast, there are no discernible distributional effects when private debt is low. This result is robust to alternative identifications of consolidations, to different ways of defining high and low debt states, and to controlling for the state of the business cycle.
Keywords: E62; E64; D63; 330